Bauran pemasaran jasa (7P) terhadap keputusan pasien dalam memilih layanan di Rumah Sakit: Literature review - Siti Alfani; Bagoes Widjanarko; Ayun Sriatmi (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: The success of a service organization such as a hospital requires a marketing strategy. Hospitals need to prepare coordination for the performance of health services so that they can meet the needs and expectations of patients.Purpose: To determine the influence of the marketing mix on patient decisions in choosing services at the Hospital.Method: This study is a Literature Review. Search for reference sources in the form of published scientific articles. References to scientific articles which discuss the service marketing mix (7P) on patient decisions in choosing services at the hospital. Collection of references through several online databases namely Science Direct, Scopus, ProQuest, Springer Link, Google Scholar, JSTOR and PubMed. The keywords used in the search are